2012
DOI: 10.1371/journal.pone.0047006
|View full text |Cite
|
Sign up to set email alerts
|

Bile Salt-Stimulated Lipase Plays an Unexpected Role in Arthritis Development in Rodents

Abstract: ObjectiveThe present study aimed to explore the hypothesis that bile salt-stimulated lipase (BSSL), in addition to being a key enzyme in dietary fat digestion during early infancy, plays an important role in inflammation, notably arthritis.MethodsCollagen-induced arthritis (CIA) and pristane-induced arthritis (PIA) in rodents are commonly used experimental models that reproduce many of the pathogenic mechanisms of human rheumatoid arthritis, i.e. increased cellular infiltration, synovial hyperplasia, pannus fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
(48 reference statements)
1
5
0
Order By: Relevance
“…The BSSL protein has previously been recognized as an important player in the inflammatory process of arthritis in rodents [15]. The data presented here clearly demonstrates that BSSL is also closely associated with inflammatory joint diseases in humans.…”
Section: Plos Onesupporting
confidence: 67%
See 2 more Smart Citations
“…The BSSL protein has previously been recognized as an important player in the inflammatory process of arthritis in rodents [15]. The data presented here clearly demonstrates that BSSL is also closely associated with inflammatory joint diseases in humans.…”
Section: Plos Onesupporting
confidence: 67%
“…In addition to its roles in dietary fat digestion and protection against viral infections, BSSL has been discovered as an essential player in inflammatory arthritis [15]. Conventional BSSL knockout mice are significantly less prone to develop collagen-induced arthritis (CIA) compared to wildtype littermates, and antibodies directed towards BSSL has been shown to mitigate disease activity in two different species and experimental models of arthritis, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is expressed in the exocrine pancreas and secreted into the intestinal lumen and is primarily acknowledged for its function in facilitating digestion and absorption of dietary fat. BSSL is also found in blood, but its role in the circulation is less clear (19). In the gastrointestinal (GI) tract, BSSL has broad specificity and hydrolyzes a variety of different substrates, for example, tri-, di-, and monoglycerides, cholesteryl and retinyl esters, phospholipids, and ceramides (20)(21)(22).…”
mentioning
confidence: 99%
“…Besides this digestive function, growing data points out that this enzyme could have an important extraintestinal function: BSDL was found to be able to traverse the intestinal mucosa towards blood circulation and was even retrieved in urines of healthy subjects [10][11][12]; it is secreted by endothelial cells and monocytes-macrophages [13,14] and several studies supported its involvement in the metabolism of lipoproteins, with impact on the cholesterol pools [15][16][17]. In link with this, it was reported that BSDL is or could be involved in pathophysiological processes, including atherosclerosis and inflammation [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%